(untitled) - Farrell, Joyce (Boston, MA., 2010)
Java Programming, Fifth Edition provides the beginning programmer with a guide to developing applications using the Java programming language. Java is popular among professional programmers because it can be used to build visually interesting GUI and Web-based applications. Java also provides an excellent environment for the beginning programmer - a student quickly can build useful programs while learning the basics of structured and object-oriented programming techniques.
Keywords: Java (Computer program language),Java ( ngôn ngữ chương trình máy tính )